Weed Dynamics and Yield of Cowpea Inoculated in Mulching (Crushed Capoeira) - Marinho, Tácila Rayene dos Santos; Reis, Régilla Martins Feitosa dos; Marques, Luiz Júnior Pereira; Corrêa, Maria José Pinheiro; Marinho, Denise Lima Cavalcante; Freitas, Antonio Carlos Reis de; Silva, Maria Rosângela Malheiros (Journal of Agricultural Studies, 2022)
Mulching (crushing capoeira) is an alternative system for the use of fire for cultivation in the Northern region of Brazil. Cowpea is considered an important food crop in this region; however, weeds might limit its productivity. This study aimed to evaluate the population dynamics of weeds and the productivity of cowpea with different habit of growth inoculated with Bradyrhizobium sp in mulching. The experiment was carried out in randomized blocks with the cultivars BRS Guariba and BR 17 Gurgueia, with and without inoculation of Bradyrhizobium sp and nitrogen fertilization as a control. Twenty-seven species and three genera of weeds were identified, distributed into 12 botanical families in the BRS Guariba cultivar and 25 species in ten families in BR 17 Gurgueia cultivar. The results revealed that the significative species were Vismia guianensis (Aubl.) Pers, Cyperus sp, Scleria melaleuca Rchb. ex Schltdl. & Cham, and Spermacoce verticillata L. Inoculation with Bradyrhizobium sp reduced the infestation of the most important species and presented higher productivity (1965.09 kg ha-1) than the treatment without inoculation (987.14 kg ha-1). The growth habit of cowpea cultivars in mulching (crushing capoeira) system did not affect crop yield, but longer studies are needed to validate the information obtained.